Initial Digital Filtering of Testing Signals of High-speed DAC - Ustinavičius, T.; Kvedaras, R.; Kvedaras, V.; Jankauskas, Z. (Elektronika ir Elektrotechnika, 2009)
Results of investigation of the digital processing algorithm for processing test signal of DAC settling time measurement are presented. It is shown that the highest influence to the measurement errors is generated by the internal noises of sampling head. Initial filtering of test signal is proposed. Spectrum components of test signal and noises are separated by generating digital pseudo-periodic test signal out of n test signal realizations and internal noise signal realizations. It is shown that standard high-pass filters are not feasible for filtering test signals because of tough requirements set to distortions of test signal. Algorithm for digital filter has been developed. It is shown by experiments that the frequency „fork” digital filter is effectively reducing low-frequency internal noises of the sampling head in the test signal. Ill. 5, bibl. 8 (in English; summaries in English, Russian and Lithuanian).